Enhancing Pain Management Strategies During Labor: a Quality Improvement Initiative - Angel G Joseph; Mubarak Hanyan Almasan; Hind Ali-Suwasis; Haya Turkey (International Journal of Allied Medical Sciences and Clinical Research, 2025)
Background: Pain during labor is one of the most intense forms of physical discomfort experienced by women, yet pain management practices often vary due to inconsistent staff training, limited use of non-pharmacological methods, and delays in documentation. Initial audits identified gaps in pain assessment, documentation, and intervention use, contributing to reduced maternal satisfaction and increased anxiety. Objectives: To improve compliance with pain assessment and timely documentation to ≥90%, ensure 100% staff training on pain relief methods, increase non-pharmacological pain relief usage, and enhance patient satisfaction with labor pain management. Methods: A pre–post interventional study was conducted from May to July 2025 in the Obstetrics & Gynecology Ward at WDGH. Interventions included staff training, standardized pain management protocols, integration of checklists, availability of non-pharmacological tools, and continuous audit-feedback cycles. Data were collected monthly using structured observation tools, documentation audits, and patient satisfaction surveys. Results: Pain score documentation improved from 58% to 91%, non-pharmacological pain relief usage increased from 30% to 76%, and patient satisfaction rose from 55% to 88%. Staff compliance with pain management protocols increased from 50% to 89%. Conclusion: Structured training, standardized protocols, and enhanced monitoring significantly improved clinical practices, patient satisfaction, and overall quality of pain management during labor. Sustaining these improvements requires ongoing training, audits, and leadership engagement.